Hypertension management: experiences, wishes and concerns among older people—a qualitative study - van Bussel, Emma (BMJ Open, 2019)
OBJECTIVES: Sixty-five per cent of older people have hypertension, but little is known about their preferences and concerns regarding hypertension management. Guidelines on hypertension lack consensus on how to treat older people without previous cardiovascular disease (CVD). This asks for explicit consideration of patient preferences in decision making. Therefore, the aim of this study was to explore older peoples’ experiences, preferences, concerns and perceived involvement regarding hypertension management. DESIGN: Qualitative interview study. SETTING: Participants were selected from 11 general practitioner (GP) practices in the Netherlands and purposively sampled until data saturation was achieved. Semistructured interviews were conducted, audio recorded and analysed by two researchers using thematic analysis. PARTICIPANTS: Fifteen community dwelling older people aged 74–93 years with hypertension and without previous CVD participated. RESULTS: Interviewees rarely started the conversation about hypertension management with their GP, although they did have concerns. Reasons for not discussing the subject included low priority of hypertension concerns, reliance on GPs or trust in GPs to make the right decision on their behalf. Also, interviewees anticipated regret of reducing medication, fearing vascular incidents. Interviewees would like to discuss tailoring treatment to their needs, deprescription of medication and ways to reduce side effects. They expected GPs to be more transparent on treatment effects. CONCLUSION: Older people describe having little involvement in hypertension management, although they have several concerns. Since GPs are also known to be hesitant to bring up this subject, we signal a conspiracy of silence about antihypertensive medication. Through breaking this silence, GPs can facilitate shared decision-making on hypertension management and better tailored care.